Brittle Characteristic and Microstructure of Sandstone under Freezing-Thawing Weathering. (21st September 2020) - Yu, Songtao; Deng, Junren; Deng, Hongwei; Gao, Feng; Li, Jielin
Abstract : As an important property of rock material, brittleness plays a vital role in rock engineering. This paper raised the concept of elastic strain energy release rate and proposed an elastic strain energy release rate based brittleness index based on the most acceptable definition of brittleness. Mechanical and Nuclear Magnetic Resonance parameters of sandstone under various Freezing-Thawing (F-T) cycles are also acquired and analyzed. Then, the proposed brittleness index is used to compare with two recently proposed brittleness indices to verify its correctness and applicability. Finally, the brittleness index is applied to evaluate the brittle behavior of F-T cycles treated sandstone under uniaxial compression. The results show that elastic modulus, value of the postpeak modulus, and peak stress decrease with F-T cycles, and the porosity and microstructure develop with F-T cycles. The proposed brittleness index is highly related to F-T cycles, peak stress, porosity, and elastic modulus of sandstone that suffered recurrent F-T cycles. It declines exponentially with F-T cycles and porosity increase while growing exponentially with peak stress and elastic modulus increase.